Three-Dimensional Scanning-Based Retrofitting of Ballast Water Treatment Systems for Enhanced Marine Environmental Protection - Zoe Kanetaki; Athanasios Iason Giakouvakis; Panagiotis Karvounis; Gerasimos Theotokatos; Evangelos Boulougouris; Constantinos Stergiou (Journal of Marine Science and Engineering, 2026)
This study investigates the integration of 3D laser scanning technology in the retrofitting of Ballast Water Treatment Systems (BWTS) on existing commercial vessels, addressing the global challenge of invasive aquatic species. The methodology combines a bibliometric analysis of keywords—indicating recent trends and knowledge gaps, a feasibility study, and detailed engineering design with on-site supervision. A case study is presented on a crude oil tanker, employing a multi-station 3D scanning strategy across the engine and pump rooms—performed using 63 and 45 scan positions, respectively. These data were processed with removal filters and integrated into specialized CAD software for detailed piping design. The implementation of high-fidelity point clouds served as the digital foundation for modeling the vessel’s existing piping infrastructure and retrofitting with the installation of an electrolysis-based BWTS. Results confirm that 3D scanning enables precise spatial analysis, minimizes retrofitting errors, reduces installation time, and ensures regulatory compliance with the IMO Ballast Water Management Convention. By digitally capturing complex onboard environments, the approach enhances accuracy, safety, and cost-effectiveness in maritime engineering projects. This work underscores the transition toward point cloud-based digital twins as a standard for sustainable and efficient ship conversions in the global shipping industry.

Hydrometallurgical recovery of silver and gold from waste printed circuit boards and treatment of the wastewater in a biofilm reactor: An integrated pilot application - Dimitrios Vlasopoulos; Panagiota Mendrinou; Paschalis Oustadakis; Pavlina Kousi; Athanasios Stergiou; Spyridon-Dionysios Karamoutsos; Artin Hatzikioseyian; Petros E. Tsakiridis; Emmanouella Remoundaki; Styliani Agatzini-Leonardou (Journal of Environmental Management, 2023)

Food web modelling on the structure and functioning of a Mediterranean lentic system - Dimitrios K. Moutopoulos; Maria Th. Stoumboudi; Alexis Ramfos; Konstantinos Tsagarakis; Konstantinos C. Gritzalis; Olga Petriki; Athina Patsia; Roberta Barbieri; Athanasios Machias; Konstantinos I. Stergiou; Dimitra C. Bobori (Hydrobiologia, 2018)